A General Equilibrium Model of Sovereign Default and Business Cycles - Yue, Zhanwei; Mendoza, Enrique (Washington, D.C. : International Monetary Fund, 2011)
Emerging markets business cycle models treat default risk as part of an exogenous interest rate on working capital, while sovereign default models treat income fluctuations as an exogenous endowment process with ad-noc default costs. We propose instead a general equilibrium model of both sovereign default and business cycles. In the model, some imported inputs require working capital financing; default on public and private obligations occurs simultaneously. The model explains several features of cyclical dynamics around default triggers an efficiency loss as these inputs are replaced by imperfect substitutes; and default on public and private obligations occurs simultaneously. The model explains several features of cyclical dynamics around deraults, countercyclical spreads, high debt ratios, and key business cycle moments.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet